Analysis of Experiences and Coping Strategies of Pregnant Women with Hyperemesis Gravidarum in Purwakarta Regency, Indonesia - Lathifah, Maulida; Sopiah Sri Rahayu (HM Publisher, 2024)
Introduction: Hyperemesis gravidarum (HG) is a pregnancy complication characterized by excessive nausea and vomiting. HG can cause dehydration, malnutrition, and other serious complications. In Indonesia, data regarding the experiences and coping strategies of pregnant women with HG is still limited. Methods: This research uses a qualitative design with a phenomenological approach. Data was collected through in-depth interviews with 10 pregnant women who experienced HG in Purwakarta Regency. Data were analyzed using qualitative data analysis methods. Results: The research results show that pregnant women with HG experience various kinds of physical and emotional symptoms. The most common physical symptoms are nausea, vomiting, fatigue, and dizziness. The most common emotional symptoms are anxiety, depression, and stress. Pregnant women use various coping strategies to deal with HG. The most common coping strategies are problem-focused coping strategies, such as seeking information about HG, consulting a doctor, and trying home remedies. Other coping strategies used are coping strategies that focus on emotions, such as seeking social support and relaxation. Conclusion: This research shows that pregnant women with HG experience a variety of physical and emotional symptoms. Effective coping strategies can help pregnant women to overcome HG and improve their quality of life.